RECLAMATION LAND OF FORMER ZIRKON MINING FOR CARBON DIOXIDE ABSORPTION MEDIUM BY EUCALYPTUS PLANTS - Herawan, Daya; Senas, Petrus; Adji, Fengky (Acta Scientiae et Intellectus, 2024)
Eucalyptus plants have a promising potential to absorb carbon dioxide in the reclamation area of the former zircon mining area. Eucalyptus was chosen as a pioneer plant because it was easy and inexpensive to propagate, plant and maintain. Selection of land reclamation plants by looking at the characteristics of the land to be planted, such as information on the physical properties of the soil, soil chemistry, rainfall, wind, temperature, topography, pests, diseases and animals that exist around the reclamation site. Research results show that carbon dioxide uptake is significant in support of its growth.